115k views
2 votes
6(2x + 3) − 4(5x + 2)

User Istan
by
5.0k points

2 Answers

4 votes

Answer:

-8x+ + 10

Explanation:

Stop deleting my answer scooby Doo, i really need points now

User Shanky
by
5.3k points
3 votes

Answer:

-8x+10

Explanation:

=(6)(2x)+(6)(3)+(−4)(5x)+(−4)(2)

=12x+18+−20x+−8

Combine Like Terms:

=12x+18+−20x+−8

=(12x+−20x)+(18+−8)

=−8x+10

User Ibrahim Muhammad
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.